Extended pelvic lymph node dissection at the time of robot-assisted radical prostatectomy: Impact of surgical volume on efficacy and complications in a single-surgeon series. - Di Pierro, Giovanni Battista; Grande, Pietro; Wirth, Johann Gregory; Danuser, Hansjörg; Mattei, Agostino (Canadian Urological Association Journal, 2015)
Introduction: We assessed the impact of surgical volume on perioperative outcomes and complications of robotic extended pelvic lymph node dissection (ePLND). Methods: From November 2008 to October 2012, a total of 233 consecutive patients with intermediate- or high-risk clinically localized prostate cancer underwent robot-assisted radical prostatectomy (RARP) and ePLND by a single, experienced open and laparoscopic surgeon. Data were prospectively collected. Complications were classified according to the Modified Clavien System. Complications potentially related to ePLND were documented. The minimum follow-up was 3 months. To evaluate the impact of surgical volume on the results, 4 patient subgroups (subgroup 1: cases 1–59; 2: 60–117; 3: 118–175; 4: 176–233) were compared using the Chi-squared and Kruskal-Wallis tests. Results: The mean (range) operative time for ePLND was 79 minutes (range: 48–144), with a steady performance over time (p = 0.784). The count of resected lymph nodes plateaued after 60 procedures (mean [range]: 13 [range: 6–32], 15 [range: 7–34], 17 [range: 8–41], 16 [range: 8–42] in Groups 1 to 4, respectively, p = 0.001). Tumour lymph node involvement was 12% in Groups 1 and 2, 7% in Group 3 and 9% in Group 4 (p = 0.075). Overall, 115 complications were reported in 98/233 patients (42%), with a significant decrease after 175 cases (p = 0.028). In Group 4, 3 patients reported an ePLND-related bleeding requiring open revision. Lymphoceles were detected in 10/233 patients (4.2%) and 1 patient (1.7%) in each of the Groups 2 to 4 required a percutaneous drainage. Conclusions: A surgeon with extensive experience is expected to achieve a safe learning curve for ePLND during RARP. A learning curve of 60 cases is suggested for optimal lymph node yield.